Industrial Specialization, Trade, and Labour Market Dynamics in a Multisectoral Model of Technological Progress - Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2001)
The issue of the impact of trade on economic performance and labour markets has been intensively discussed in the recent literature on trade liberalization and globalization where the debate was mainly about identifying the relative impact of trade and technology. The bulk of the existing literature in this area employs almost without exception a static Heckscher-Ohlin framework which seems not to be a suitable tool for analysing the ongoing dynamics. This paper presents a dynamic multi-sectoral framework with heterogenous labour to explore the issue of trade liberalization and sectoral catching-up in productivity levels. The model is basically an input-output framework with Schumpeterian features; the latter are modelled as the impact of transitory rents which result from uneven productivity growth and technological catching-up upon the price and quantity systems of the trading economies. Relative productivity and wage rate dynamics across sectors determine the comparative costs and the dynamics of trade specialization. In the appendix the equilibrium solutions of the model are derived.
Keywords: C62; C63; C67; D57; F15; F17; 330; trade liberalization; economic integration; labour markets; simulation; economic dynamics; growth